Issues on the Chinese Language and the Sinitic Languages - Uliana, Chiara (Sinología hispánica. China Studies Review, 2020)
The most used language in China is defined by many different terms, among which Hanyu 汉语, Zhongwen 中文, putonghua 普通话, guoyu 国语, Zhongguohua 中国话. Some of them have been translated into Western languages , into Spanish, English, Italian and other languages, in each one of those there are several terms used to refer to it. The lack of agreement on the nomenclature can be considered an indicator of a broader underlying disagreement. The bases of this disagreement rest on several pillars that will be analyzed in this work.